Venesection in hypovolemic shock - Kshetri, Samir; Dhami, Keshav Singh; Oli, Bikram; KC, Rajendra; Kakshapati, Neelam (Journal of General Practice and Emergency Medicine of Nepal, 2023)
A 20-year-old female, a referred case, from health post presented to emergency department of Manthali hospital Ramechhap, with history of loose watery stool and vomiting for 4 days. On primary survey examination - Airway; patent with no c-spine tenderness, breathing; no chest retractions, no obvious injury, oxygen saturation was 94% in room air. Pulse was 160 beats per minute, feeble; blood pressure was not recordable; cold clammy and bluish discoloration of skin was noted. Intravenous cannulation was tried but could not succeed. GCS= 15/15, bilateral pupil was round, regular and reactive, there was no focal neurological deficit. Multiple prick mark for intravenous cannulation was seen. With appropriate counselling and consent, vein-section was done. An incision of about three centimeters was given just one centimeter above left medial malleolus. A 16-gauze intravenous cannula was inserted at left long saphenous vein and fixed with prolene 2. Eight pint of warm normal saline and one pint of Haemaccel was transfused. After stabilizing her bluish limbs turned into pink; her sadness turned into happiness. She was referred to higher center and was admitted for 4 days and discharged with a diagnosis of acute gastroenteritis with prerenal acute kidney injury(resolved). Gastrointestinal losses like diarrhea and vomiting can lead into hypovolemic shock which is fatal. Fluid resuscitation is the mainstay of therapy in patients with severe hypovolemia.